Association between pathologic grade and multiphase computed tomography enhancement in pancreatic neuroendocrine neoplasm. Issue 9 (17th April 2018) - Kang, Jinwoo; Ryu, Ji Kon; Son, Jun Hyuk; Lee, Jae Woo; Choi, Jin Ho; Lee, Sang Hyub; Kim, Yong‐Tae
Abstract: Background and Aim: Pancreatic neuroendocrine neoplasms (PanNENs) are rare diseases but gradually increasing in prevalence with different prognosis. Multiphase contrast‐enhanced computed tomography (CT) is known as widely used imaging modality for the diagnosis of pancreatic tumors. We aimed to investigate whether CT enhancement pattern is associated with the pathologic tumor grade and can predict that of PanNEN. Methods: Ninety PanNEN patients who underwent multiphase enhanced CT before pathologic diagnosis were retrospectively reviewed. CT enhancement values at each phase were measured, and its relation with pathologic grade was assessed. Results: Ninety PanNENs included 62 G1 (68.9%), 21 G2 (23.3%), and 7 G3 (7.8%). The enhancement values of the early arterial phase were significantly different among three groups (G1 119.4 HU, G2 94.7 HU, and G3 64.8 HU; G1 vs G2, P = 0.043; G1 vs G3, P = 0.001; and G2 vs G3, P = 0.027). In the late arterial phase, there was a difference between grade 1/2 and 3 but no significant difference between grade 1 and grade 2 (G1 164.3 HU, G2 142.9 HU, and G3 94.1 HU; G1 vs G2, P = 0.804; G1 vs G3, P = 0.016; and G2 vs G3, P = 0.022). The enhancement value of the portal phase did not differ significantly among the three groups. Diagnostic ability of the early arterial enhancement value for the differentiation of the G1 (cutoff 109.5 HU, sensitivity 73.3%, and specificity 62.5%) was comparable with that of the tumor size (cutoff 20.5 mm, sensitivity 68.9%, and specificity 66.7%). Conclusions: Computed tomography enhancement value at early arterial phase and its changing pattern can be a useful predictor for the differentiation of pathologic grade of PanNENs.